PENGARUH INSENTIF PAJAK, KUALITAS PELAYANAN FISKUS, PENERAPAN E-FILING DAN KESADARAN PAJAK TERHADA P KEPATUHAN WAJIB PAJAK UMKM PADA MASA PANDEMI COVID-19 (Studi Empiris Wajib Pajak UMKM di KPP Pratama Kota Solok 2019-2020) - Fatihan Maysha Nadira; Zirman Zirman; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study is to evaluate and analyze the following: (1) the effect of tax incentives on taxpayer compliance, (2) the effect of tax service quality on taxpayer compliance, (3) the effect of the implementation of e-filing on taxpayer compliance, and (4) awareness tax on taxpayer compliance. The population in this study were MSME taxpayers registered at the KPP Pratama Solok City. In this study, using a purposive sampling technique. This study uses primary data by distributing questionnaires. The data analysis method used in this research is Statistical Product and Service Solutions (SPSS). The results showed that the variables of tax incentives, service quality of the tax authorities, the implementation of e-filing and tax awareness had an effect on MSME taxpayer compliance.Keywords: Tax Incentives, Quality Fiscal Service, Implementation of E-filing, Tax Awareness, Taxpayer Compliance